Implementasi Peraturan Bupati Langkat Nomor 4 Tahun 2021 Dalam Rangka Meningkatkan Disiplin Kesehatan di Desa Pulau Sembilan Kecamatan Pangkalan Susu - Putrama Al Khairi; Dedi Amrizal (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
This research was conducted in the village of Pulau Sembilan, Pangkalan Susu Subdistrict, Langkat. The purpose of this study was to determine whether or not the Langkat Regent's Regulation No. 4 of 2021 in order to improve health discipline in Pulau Sembilan Village has been implemented. The type of research used is descriptive method with qualitative data processing, namely the method used to dissect a phenomenon and event and describe it in the form of sentences and language based on the findings in the field. Based on the results of the research that has been carried out, it is known that the Langkat Regent's Regulation Number 4 of 2021 has been implemented but has not been fully optimal. This can be seen based on the categorization of research such as the existence of actions in achieving goals that have not been carried out optimally due to the lack of actions and programs carried out by the Pulau Sembilan village government in improving health discipline, the interaction between the government and the community in the form of education and socialization but so far it has not produced results. as expected, the implementation of administrative activities in the form of planning and implementing work procedures although it is still not efficient, the existence of sanctions given by the Pulau Sembilan village government to people who violate the health protocol policy rules even though it is only in the form of giving a warning. The obstacle to improving the health discipline of the Pulau Sembilan village community so far is the lack of firmness by the Pulau Sembilan village government in giving sanctions to violators of the rules in an effort to improve health discipline and a sense of the importance of maintaining health from within the community